MANAGEMENT OF RAISING FINANCIAL RESOURCES OF THE ENTERPRISE ON THE BASIS OF THE FINANCIAL RISK RATIO TARGETING - FORKUN, IRYNA; GORDEEVA, TETYANA (Herald of Khmelnytskyi National University. Economic sciences, 2021)
The article analyzes the essential characteristics and modern approaches to raising different types of financial resources by enterprises in order to ensure continuous operation.Raising financial resources is a master goal of financial activity. It is substantiated that sufficient financial security in case of lack of equity causes borrowing financial resources, which leads to changes in the size and composition of equity and liabilities of the enterprise. The efficiency of financial activities can be assessed through the balance between own and borrowed financial resources. However, financial risks are closely related to the lack or the probability of loss of financial resources due to changes in prices, interest rates, exchange rates, changes in the activities of the industry or a particular borrower. They are the most threatening and destructive for the company, and therefore require constant monitoring, evaluation and minimization. The assessment of the quality of raising financial resources should be considered according to the balance sheet of the enterprise operating in the telecommunications market. This market is chosen because of its rapid development due to global trends. It is proposed to manage the financial resources of the enterprise on the basis of targeting the financial risk ratio, which provides for the establishment of targets for the allowable value of the financial risk ratio and allows a better approach to the formation of borrowed capital (liabilities). The integrated indicator of the quality of raising financial resources by the enterprise is constructed, which allows to calculate forecast scenarios and to make administrative decisions. Therefore a choice of strategy for raising financial resources should be made taking into account all factors of influence and risks.
Keywords: financial resources; liabilities; financial risk; forecasting; integral indicator of the quality of raising financial resources